2017
DOI: 10.1093/nar/gkx880
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into RNA unwinding and degradation by RNase R

Abstract: RNase R is a conserved exoribonuclease in the RNase II family that primarily participates in RNA decay in all kingdoms of life. RNase R degrades duplex RNA with a 3′ overhang, suggesting that it has RNA unwinding activity in addition to its 3′-to-5′ exoribonuclease activity. However, how RNase R coordinates RNA binding with unwinding to degrade RNA remains elusive. Here, we report the crystal structure of a truncated form of Escherichia coli RNase R (residues 87–725) at a resolution of 1.85 Å. Structural compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 41 publications
4
41
0
Order By: Relevance
“…Based on sequence alignments with the related RNase Rs, the residues (Thr 646, Phe 654, Leu 665 and His 667) were identified as the catalytic sites in the sequence of PsRNR (Figure 1). However, RNase R from E. coli DEC6A was seen to have two catalytic sites (Asp 272 and Asp 281) [15]. Besides, it was reported that two catalytic sites from E. coli were identified in Tyr 324 and Asp 280 [16].…”
Section: Resultsmentioning
confidence: 99%
“…Based on sequence alignments with the related RNase Rs, the residues (Thr 646, Phe 654, Leu 665 and His 667) were identified as the catalytic sites in the sequence of PsRNR (Figure 1). However, RNase R from E. coli DEC6A was seen to have two catalytic sites (Asp 272 and Asp 281) [15]. Besides, it was reported that two catalytic sites from E. coli were identified in Tyr 324 and Asp 280 [16].…”
Section: Resultsmentioning
confidence: 99%
“…Based on these findings, the intrinsic helicase activity of RNase R is essential for its proper functioning in vivo . The crystal structure of a truncated form of E. coli RNase R has been determined recently and reveals that the protein has two RNA-binding channels and that it contains a ‘wedge’ region that appears to induce RNA unwinding (Chu et al 2017). How the ‘wedge’ relates to the intrinsic RNA helicase activity remains to be determined.…”
Section: Escherichia Coli Exoribonucleasesmentioning
confidence: 99%
“…It was noticed that the impaired maturation of the rrn5S transcript in the mutant is associated with the accumulation of an antisense RNA (asRNA), and this defective maturation was recapitulated in transplastomic plants artificially overexpressing the asRNA (Hotto et al, 2010;Sharwood et al, 2011b). Based on the ability of the E. coli enzyme to unwind RNA duplexes in vitro, it can be speculated that RNR1 might degrade the asRNA in vivo Sharwood et al, 2011b;Chu et al, 2017). A more thorough investigation of the rnr1 RNA patterns also demonstrated the essential role of the enzyme in mRNA 39 maturation, in cooperation with PNPase.…”
Section: Rnr1mentioning
confidence: 99%